2017
DOI: 10.1007/s11856-017-1456-4
|View full text |Cite
|
Sign up to set email alerts
|

Rank three Nichols algebras of diagonal type over arbitrary fields

Abstract: Over fields of arbitrary characteristic we classify all rank three Nichols algebras of diagonal type with a finite root system. Our proof uses the classification of the finite Weyl groupoids of rank three.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In this section, we recall the notations of semi-Cartan graphs, root systems, and Weyl groupoids. We mainly follow the terminology from [20,39] (see also [35][36][37]). Definition 6.…”
Section: Weyl Groupoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we recall the notations of semi-Cartan graphs, root systems, and Weyl groupoids. We mainly follow the terminology from [20,39] (see also [35][36][37]). Definition 6.…”
Section: Weyl Groupoidsmentioning
confidence: 99%
“…Towards this direction, new examples of Nichols algebras in positive characteristic and a combinatorial formula to study the relations in Nichols algebras were found [34]. Over fields of positive characteristic, rank 2, rank 3, and rank 4 finite dimensional Nichols algebras of diagonal type were listed in [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If λ 2 = 0 = µ 1 , then µ 3 = 0 and we can take µ 4 ∈ I 0,1 by rescaling x, which gives two classes of H described in (32) and (33).…”
mentioning
confidence: 99%
“…Towards this direction, new examples of Nichols algebras in positive characteristic and a combinatorial formula to study the relations in Nichols algebras were found [11]. Over fields of positive characteristic, rank 2 and rank 3 finite dimensional Nichols algebras of diagonal type were listed in [25,38]. In…”
mentioning
confidence: 99%